Comparison of the analysis and structural design between the Ibague seismic microzoning and the NSR-10 regulation - Toro Ruíz, Jean Paul Alejandro; Quintero Pinzón, Juan Sebastián; Del Río Gaitán, Juan David (Universidad Pedagógica y Tecnológica de Colombia - UPTC, 2021)
Structural design is an essential field in civil engineering and in the development of society, since it provides safe and efficient structural systems for the several types of buildings and civil works necessary to improve the quality of life of its users and occupants. Considering this situation, in this project, it was carried out a study in the city of Ibague in which it was sought to determine and compare the variables required to design a reinforced concrete structure. For this reason, the seismic amplification coefficients of the Colombian Seismic Resistant Construction Regulation (NSR-10) given for the most common types of soil in Ibague and the current seismic microzoning of the city are compared, which affect and generate a variation in the design earthquake. In addition, the study of the energy dissipation capacity of the structure was proposed to generate a complete analysis of the design variables and obtain safe and optimal parameters and recommendations for the execution of the structural design of regular buildings with less than 5 floors. The BIM Revit tool was used, which allows to have complete information of the structural project related to the materials and thus estimate the variations between the different designs obtained.